ASSOCIATION OF RADIAL ARTERY ACCESS WITH REDUCED INCIDENCE OF ACUTE KIDNEY INJURY - RAZA , MT; AKHTAR, B; BABAR, SM; MAL, K; RIZVI, SNH (Biological and Clinical Sciences Research Journal, 2024)
Acute kidney injury (AKI) is a serious complication following cardiac procedures, leading to increased morbidity and mortality. The choice of vascular access site may influence the incidence of AKI, with radial artery access potentially offering protective benefits compared to femoral artery access. Objective: To evaluate the association between radial artery access during cardiac procedures and the incidence of acute kidney injury among patients. Methods: This retrospective cohort study was conducted at the National Institute of Cardiovascular Disease from January 2023 to January 2024. A total of 370 patients who underwent cardiac procedures were included, comprising 200 patients in the radial artery access group and 170 in the femoral artery access group. Data were collected retrospectively from medical records, including demographic information, baseline renal function, procedural details, and serum creatinine levels before and after the procedure. The incidence of AKI was determined based on established criteria for changes in serum creatinine. Statistical analyses were performed using appropriate tests, with a significance level set at p < 0.05. Results: Patients in the radial artery access group had a shorter average hospital stay (2.5 ± 1.2 days) compared to the femoral group (3.8 ± 1.5 days, p = 0.001). The mortality rate was lower in the radial group (1.5%) versus the femoral group (4.1%), although this difference was not statistically significant (p = 0.09). The incidence of major adverse cardiovascular events (MACE) was 2.5% in the radial group compared to 5.9% in the femoral group (p = 0.07). Acute kidney injury occurred in 10.0% of patients in the radial artery access group (20 out of 200) versus 17.6% in the femoral artery access group (30 out of 170), indicating a significant reduction in AKI incidence with radial access. Conclusion: Using radial artery access during cardiac procedures significantly reduces the incidence of acute kidney injury compared to femoral artery access. These findings support the preference for radial artery access to minimize the risk of AKI and improve patient outcomes.